Application of whey protein and pea starch edible coatings with citric acid: impact on the quality and texture of dried apple and potato slices - Ghadeer F. Mehyar; Nihad G. Alsmairat; Zaina A. Fahil; Dana M. Alangar; Nour T. Hasan; Salam A. Ibrahim (Discover Food)
Abstract The effect of whey protein isolate (WPI), pea starch (PS), and composite coatings (WPI + PS), with or without the incorporation of citric acid (CA), on the physicochemical, color, microbial, textural, and sensory properties of dried apple and potato slices was investigated. All coatings reduced the browning index (BI) and increased the moisture content of the samples. The incorporation of CA increased acidity, lowered pH, and minimized the BI, with the PS-CA coating on apples achieving the lowest BI (0.15). Coatings containing CA enhanced the samples’ lightness (L*), yellowness (b*), and chroma than those without CA. The PS-CA coating maintained color closest to that of the fresh samples, exhibiting the lowest ∆E values. PS-CA and WPI + PS-CA coatings were the most effective in reducing mesophilic aerobes, coliforms, and yeasts and molds, achieving the highest reductions in coliform counts (2.6 log CFU/g and 1.9 log CFU/g, respectively) in apple slices. All coatings improved the fracturability, crunchiness, and hardness work of the samples, with the presence of CA further enhancing the textural properties. The PS-CA coating resulted in the highest crunchiness and hardness work (8.1 and 23.9 MJ, respectively), and the lowest fracturability (489.9 g). Coated samples exhibited lower stiffness, with fractures occurring approximately 8 s earlier in apple slices. The coatings improved sensory lightness, shrinkage, glossiness of apple slices, and overall acceptability. Active edible coatings containing CA effectively mitigated the deteriorative effects of drying on minimally processed apples and potatoes, with the PS-CA coating emerging as the most effective treatment.